GEOMORPHIC CONSTRAINS ON THE EVOLUTION OF THE AGGITIS RIVER BASIN NORTHERN GREECE (A PRELIMINARY REPORT) - Pennos, Ch.; Lauritzen, S.E.; Pechlivanidou, S.; Sotiriadis, Y. (Bulletin of the Geological Society of Greece, 2016)
In this paper we discuss the landscape evolution of the Aggitis River basin by correlating the morphological characteristics of the Maaras Cave (Aggitis River spring) with the main geomorphological features of the Aggitis fluvial valley. We combine the various morphological features that are hidden inside the Maaras Cave with the surface geomorphology of the river valley in order to trace the imprint of the different evolutionary stages on the landscape. Also, we provide a relative chronological framework for the evolution of the area. The 3D survey of the Maaras Cave shows that the roof of the cave is looping-like shaped in contrast to the floor of the cave that shows low slopes and holds thick clastic sediment deposits. Furthermore, the geomorphological mapping of the Aggitis River valley shows two prominent windgaps at the southern part of the basin that formed as the result of river capture. Our results suggest that the Aggitis River basin suffered four major evolutionary stages from the Neogene until the Quaternary.